Introduction to Philosophy of Sports Tourism - Made Pramono; Mokhamad Nur Bawono; Agus Satmoko Adi; Nurhasan (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The Indonesian government has prioritized cultural and agricultural tourism. In Indonesia, administrators disregard the policies regarding sports tourism. Numerous nations rely on sports tourism for economic growth. Thus the economic worth of sports tourism is, without a doubt, remarkable. This investigation seeks to identify the beliefs that contribute to sports tourism. The research also seeks to assess the influence of sports' moral, ethical, and aesthetic philosophy on Indonesia's sports tourism culture. Respondents' primary data were collected for the study's findings. The studies revealed that ethical, moral, and aesthetic beliefs substantially impacted sports tourism. This study is motivated by a vacuum in the existing literature and aims to provide a comprehensive introduction to sports philosophy. Thus, this study has significant theoretical ramifications and contributes significantly to the literature on sports tourism. Similarly, the research's practical implications provide a path forward for the Indonesian government to acknowledge these sports ideologies to promote sports tourism. In its conclusion, the study has considered the key future areas that scholars must pursue to contribute additional material to the body of knowledge.